Development of a patient decision aid for men with spinal cord injury making a decision on the method of bladder drainage: the bladder explorer / Julia Patrick Engkasan - Julia , Patrick Engkasan (2017)
Background: Bladder dysfunction is common following a spinal cord injury (SCI) and this necessitates the use of an alternative method to empty the bladder. Making this decision is difficult because it needs considerable knowledge and patients are still adjusting to the recently acquired disability. Furthermore the pros and cons of each treatment options have variable effects on a person’s life. The aim of this study is to develop a patient decision aid to help men with SCI make this decision. Methods: This study consisted of two phases: Phase I explored how decision on bladder drainage method was made in the local context. Ten rehabilitation professionals, 17 men with SCI, and four family members were interviewed individually. This study revealed that men with SCI did not participate actively and were not sufficiently informed when making this decision. This led to the development of an iPad-based patient decision aid called Bladder Explorer (BE). BE underwent a systematic development process, which included: project group formation, content development, application design and development, and prototype refinement. The steering committees oversee the whole development process and consisted of rehabilitation professionals, urologists, decision experts, consumers and technology expert. The content and design was informed by the International Patient Decision Aid Standards (IPDAS) collaboration quality dimensions, the cognitive theory of multimedia learning, needs assessment results, and literature review. Alpha testing were done in stages using different format of BE; word document in alpha test I, low-fidelity prototype in alpha test II, and high-fidelity prototype in alpha test III. The BE was beta-tested with five real-life users to assess its usability, acceptability, utility and feasibility. This beta test used a mixed method design; the qualitative approach used screen recording, fields notes and semi-structured interviews whilst the quantitative approach used System Usability Scale (SUS) and Acceptability questionnaire. iv Results: The review-revision cycle of the alpha test took seven iterations. Alpha test I highlighted the quandary of adding “Do Nothing” as one of the treatment option. In alpha test II, aesthetic issues such as screen layout, color, fonts and icons were revised. Alpha test III uncovered functional issues such as operation of videos, navigation and the interactive component of the value clarification exercises. The resulting prototype was a 23-screen application consisting of five modules: Introduction, The Urinary System, Your Options, Stories, and Making the Decision. Beta testing of BE demonstrated that a majority of users reviewed the application favorably. The average usability score was 75 (range 67.5 to 92.5). All except one domains of the acceptability questionnaires (presentation of information, clarity, quantity of information, usefulness for decision–making, addresses their concerns, and overall length) received positive responses. The modules “Your options” and “Making the Decision” were cited most useful modules. Barriers to implementation include determining the entry point into the clinical pathway, lack of privacy, fatigue and touchscreen illiteracy. There was no major revision made after the first beta test. Conclusion: BE application is acceptable, usable, and useful for men with SCI who are making decision on the method of bladder drainage.